Mengatasi Kegagalan Fruit-Set dengan Pembuangan Bekas Tandan Bunga dan Anakan Pada Salak Gula Pasir (Salacca zalacca var. Gula Pasir) - SAPUTRA, I WAYAN EKA; WIRAATMAJA, I WAYAN; RAI, I NYOMAN (Agrotrop : Journal on Agriculture Science; Vol 5 No 1 (2015))
Overcoming the Failure of Fruit-set by Removing Former Flower Stem and Shoot on Salak Gula Pasir Fruit (Salacca zalacca var. Gula Pasir). This research aimed to overcome the failure of fruit-set by removing former flower bunch and shoot on salak gula pasir (Salacca zalacca var. Gula Pasir). This research was a factorial experiment, designed using randomized completely block design with 2 factors. The first factor was removal of former flower bunch, consisted of 2 levels (removed and not removed), and the second factor was removal of shoot, consisted of 2 levels (removed and not removed). Thereby, there were 4 treatments combination and replicated 7 times so that 28 plants was required. The result of the research showed that the greatest percentage of fruit-set (80,15%) was obtained on the shoot removal treatment, whereas the fruit-set of the treatment on which shoot was not removed was 60,34%. On the removal of former flower bunch treatment, there was no significant difference on removal and not removal treatment between the percentages of fruit-set.
Keywords: Shoot, Former Flower Stem, Fruit-set, Salak Gula Pasir